Penyusunan Perjanjian Kerja Waktu Tertentu (PKWT) Menurut Undang-Undang Nomor 6 Tahun 2023 - Eloi Turnip; Rahayu Subekti; Purwono Sungkowo Raharjo (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2023)
The state is responsible for providing a decent livelihood for all its citizens. When it comes to workforce absorption, it can be divided into external and internal factors. External factors are influenced by the level of economic growth, inflation, unemployment, and interest rates. Matters regarding internal factors are addressed in the employment agreement between workers and employers, specifically focusing on fixed-term employment agreements. This research is conducted in a normative manner through library research by studying academic literature related to the issues under investigation to obtain theoretical and legal foundations related to the discussed topics or problems being studied. Normative legal research includes data obtained from library studies, consisting of legal provisions, newspapers, legal magazines, journals, and others. The process of drafting Fixed-Term Employment Agreements (PKWT) includes information about the company and the worker. The company, as the employer, is obligated to provide the company's name, address, and type of business. In line with the principles of a welfare state, the government is responsible for providing a minimum standard of living to achieve a prosperous life. Rights and obligations for both the company and the worker must be fulfilled. The formal arrangement of Fixed-Term Employment Agreements (PKWT) is designed to provide clarity in the agreement. The substantive content of the drafting of Fixed-Term Employment Agreements (PKWT) provides legal protection for both workers and companies in case of violations by either the company or the workers related to the work being carried out or actions by the company that violate the regulations of Law Number 6 of 2023.